If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(k + -1) + -5 = -2(k + -6) Reorder the terms: -7(-1 + k) + -5 = -2(k + -6) (-1 * -7 + k * -7) + -5 = -2(k + -6) (7 + -7k) + -5 = -2(k + -6) Reorder the terms: 7 + -5 + -7k = -2(k + -6) Combine like terms: 7 + -5 = 2 2 + -7k = -2(k + -6) Reorder the terms: 2 + -7k = -2(-6 + k) 2 + -7k = (-6 * -2 + k * -2) 2 + -7k = (12 + -2k) Solving 2 + -7k = 12 + -2k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '2k' to each side of the equation. 2 + -7k + 2k = 12 + -2k + 2k Combine like terms: -7k + 2k = -5k 2 + -5k = 12 + -2k + 2k Combine like terms: -2k + 2k = 0 2 + -5k = 12 + 0 2 + -5k = 12 Add '-2' to each side of the equation. 2 + -2 + -5k = 12 + -2 Combine like terms: 2 + -2 = 0 0 + -5k = 12 + -2 -5k = 12 + -2 Combine like terms: 12 + -2 = 10 -5k = 10 Divide each side by '-5'. k = -2 Simplifying k = -2
| 26=6(5+-1a) | | 7x+15=3(2-y) | | 5z+15=4z+5 | | y^2+4=400 | | [x/3-6]=(2x+4)(-1/2) | | 8y-3=-3 | | 20=3-(z+10) | | 3x+30=x | | -3(t-2)+9t=8t-6 | | -31-a=-(1-4a) | | 3x+30= | | -3(5y-9)-y=-3(y-3) | | 4(3+3x)-1=47 | | 5-2y=11-8y+6y | | .66m-.6m=4 | | 3x-6+6x=-15 | | 6(-2x-2)=-72 | | 1+3n-5n-4=1-4n | | 93-(7x+12)=7(x+3)+x | | .5xh+.33x(h-6)=.83xh+2 | | -5(t-5)+8t=6t-1 | | 5x-5=-3x-9 | | (x/3-6)=(2x+4)(-1/2) | | 3(y-5)-5y=5y+9 | | 8-4z=16 | | 7x-8=7x-8 | | 8x-3y=6-4x | | 13=.167x+2y | | -3(t-4)+7t=8t-6 | | 4x+3y+2x+y= | | -7(t-2)-(t+1)=4 | | 5y^2-2y+4=0 |